1996
DOI: 10.1046/j.1365-2141.1996.d01-1842.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human thrombopoietin in nonhuman primates with chemotherapy‐induced thrombocytopenia

Abstract: We examined the effects of recombinant human thrombopoietin (rhTPO) on myelosuppressive chemotherapy-induced thrombocytopenia in cynomolgus monkeys. After treatment with nimustine (ACNU) on day 0, the monkeys intravenously received rhTPO at a dose of 0.04, 0.2 or 1 microgram/kg/d or monkey's serum once each day from day 1 to day 28. Administration of rhTPO reduced the severity of thrombocytopenia and accelerated the rate of platelet recovery in a dose-dependent fashion. Treatment with the highest rhTPO dose co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…As a therapeutic agent TPO has been shown to speed platelet recovery following myelosuppressive therapy in cancer patients receiving chemotherapy (7,8). In addition, the biological effects of TPO are not limited to the MK lineage; the growth of erythroid (burst forming unit-erythrocyte) and myeloid (colony forming unit-granulocyte macrophage) colony-forming cells is also expanded by TPO in vitro, and its use in normal and myelosuppressed mice and non-human primates leads to enhanced recovery of multiple hematopoietic lineages (9,10). Finally, TPO affects the survival and proliferation of primitive hematopoietic stem cells in vitro (11,12) and in vivo (13).…”
Section: Thrombopoietin (Tpo)mentioning
confidence: 99%
“…As a therapeutic agent TPO has been shown to speed platelet recovery following myelosuppressive therapy in cancer patients receiving chemotherapy (7,8). In addition, the biological effects of TPO are not limited to the MK lineage; the growth of erythroid (burst forming unit-erythrocyte) and myeloid (colony forming unit-granulocyte macrophage) colony-forming cells is also expanded by TPO in vitro, and its use in normal and myelosuppressed mice and non-human primates leads to enhanced recovery of multiple hematopoietic lineages (9,10). Finally, TPO affects the survival and proliferation of primitive hematopoietic stem cells in vitro (11,12) and in vivo (13).…”
Section: Thrombopoietin (Tpo)mentioning
confidence: 99%
“…Two forms of the recombinant human protein have been investigated: full-length glycosylated recombinant human protein (rHuTPO) [5] and PEGylated megakaryocyte growth and development factor (PEG-rHuMGDF) [6]. In mice, dogs, and primates [7][8][9][10][11][12][13][14], rHuTPO and PEG-rHuMGDF promote platelet production and reduce chemotherapy-induced thrombocytopienia. Unfortunately, evidence of TPO-neutralizing antibodies in patients participating in cancer and platelet donor clinical trials forced the discontinuation of PEG-rHuMGDF development [15].…”
Section: Introductionmentioning
confidence: 99%
“…TPO has been characterized as the primary physiologic regulator of MK and PLT development [11,27,[33][34][35][36][37]. Preclinical trials in rodents and nonhuman primates substantiate its ability to promote enhanced MK and PLT regeneration subsequent to radiation and/or chemotherapyinduced myelosuppression [11,13,14,20,38,39]. Furthermore, a wide range of studies has indicated that TPO has profound effects on early hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%